2021
DOI: 10.2298/vsp191229034a
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid and intracerebral hemorrhage in cocaine abusers

Abstract: Uvod/cilj: Kokain je alkaloid iz lišća biljke Erythroxylym coca i Erythroxylym novogranatense. Unosi u organizam oralno, intranazalno, intravenski i inhalatorno, intragenitalno. Zloupotrebom kokaina može nastati subarahnoidalno i intracerebralno krvarenje. Cilj rada je prikazati koncentracije kokaina i benzoilekgonina u telesnim tečnostima i organima, učestalost subarahnoidalnog i intracerebralnog krvarenja i povezanost pomenutog krvarenja sa koncentracijama kokaina/benzoilekgonina. Metode: Analizirano je 26 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…The risk of experiencing an ICH was found to be more prominently increased with recent cocaine use than the risk of an ischemic stroke. [ 30 , 31 ] A direct correlation was reported between the concentrations of cocaine or cocaine-related metabolites in the body and the incidence of ICH or SAH [ 43 ]. In contrast, stroke severity measures at the time of admission, including Hunt and Hess (HH) score, Fisher grade, World Federation of Neurological Surgeons (WFNS) grade, and the proportion of patients with a Glasgow Coma Score < 8, showed no statistically significant difference between cocaine users and non-users across five studies [ 20 , 26 , 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of experiencing an ICH was found to be more prominently increased with recent cocaine use than the risk of an ischemic stroke. [ 30 , 31 ] A direct correlation was reported between the concentrations of cocaine or cocaine-related metabolites in the body and the incidence of ICH or SAH [ 43 ]. In contrast, stroke severity measures at the time of admission, including Hunt and Hess (HH) score, Fisher grade, World Federation of Neurological Surgeons (WFNS) grade, and the proportion of patients with a Glasgow Coma Score < 8, showed no statistically significant difference between cocaine users and non-users across five studies [ 20 , 26 , 29 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yet, three studies reported more severe HH scores upon admission in patients enduring cocaine-associated SAH [ 12 , 24 , 27 ]. One study drew an association between a positive toxicology upon admission and stroke severity [ 43 ]. Interestingly, the severity of ischemic stroke, as gauged by the NIH Stroke Scale, was not distinctively different between cocaine users and non-users [ 16 , 33 , 36 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies report SAH, ICH, IS and aneurysmal subarachnoid hemorrhage (aSAH) in cocaine-positive subjects [ 50 , 51 , 53 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Neuropathological Findings In Drug Abusersmentioning
confidence: 99%